Analysis of a flat-plate solar collector / Plokščiojo saulės kolektoriaus tyrimas - Andrius Klevinskis; Vytautas Bučinskas (Mokslas: Lietuvos Ateitis, 2012)
The paper deals with a flat plate solar collector. The experiment was conducted using the finite element method and described the theoretical effectiveness of the flat solar collector as well as the factors that produce the major loss of heat. Investigation has concentrated on several different transparent surfaces used for determining the efficiency of the collector: 5 mm thick transparent glass and 5 mm thick transparent glass coated with a film of 120 μm.